Topochemical reactions of layered transition-metal oxides - Hayward, M (Institute of Physics Publishing, 2014)
Low-temperature topochemical reactions performed on complex transition metal oxides allow the synthesis of novel, metastable phases often with unusual transition metal oxidation states and/or coordination geometries. Layered materials offer many opportunities to control the structural and chemical selectivity of these types of reactions to allow the preparation of desired phases in a rational manner. Using complex oxides adopting Ruddlesden-Popper type structures as examples, recent progress in the low-temperature topochemical reduction by anion de-intercalation, and oxidation by anion insertion, is reviewed. © 2014 IOP Publishing Ltd.